2021
DOI: 10.1111/jpc.15333
|View full text |Cite
|
Sign up to set email alerts
|

Early neonatal death review from two provinces in Papua New Guinea: A retrospective analysis

Abstract: Aim To determine the causes of early neonatal death and the avoidable factors associated with these deaths among women participating in a cluster‐randomised crossover trial in Papua New Guinea. Methods Early neonatal deaths were identified by retrospective chart review of the Women and Newborn Trial of Antenatal Interventions and Management study participants between July 2017 and January 2020. Causes of death and avoidable factors were identified using the Perinatal Problem Identification Program system. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Only half of the facilities in our study conducted regular perinatal morbidity and mortality audits. Investigations or audits of perinatal morbidity and mortality cases are important and provide an opportunity for clinicians to understand more about individual cases, gain insights into avoidable practice and systems issues, drive changes in clinical practice and stimulate quality improvement initiatives [ 21 , 62 – 64 ]. In addition, this information can be used to instigate research and inform public health initiatives to avoid future preventable newborn deaths and stillbirths [ 62 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only half of the facilities in our study conducted regular perinatal morbidity and mortality audits. Investigations or audits of perinatal morbidity and mortality cases are important and provide an opportunity for clinicians to understand more about individual cases, gain insights into avoidable practice and systems issues, drive changes in clinical practice and stimulate quality improvement initiatives [ 21 , 62 – 64 ]. In addition, this information can be used to instigate research and inform public health initiatives to avoid future preventable newborn deaths and stillbirths [ 62 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stillbirth rates are estimated to be between 20 to 30 per 1000 live births [ 20 ]. A review of 35 early neonatal deaths among 2499 live births across two provinces in PNG (East New Britain and Madang) identified several preventable causes and avoidable factors associated with these deaths, including insufficient resources at health facilities, poor quality of care during labour and birth, and poor management of high-risk newborns, including neonatal resuscitation [ 21 ]. Similarly, a review of stillbirths across the same two provinces identified at least one avoidable factor for 95% of the 59 stillbirths reviewed, included health personnel-associated factors related to poor intrapartum care and lack of early diagnosis and intervention of complications [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Cav3.2 and SERCA2a level was elevated in the PTL myometrium along with the decreased miR-25-3p, proposing that miR-25-3p and its targets may contribute to the PTL. The colonization of Gram-negative germs is a pivotal risk factor for PTL [ 43 , 44 ]. LPS can induce preterm labor by evoking the release of proinflammatory cytokines and is sometimes used to mimic infection-related PTL in murine [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research from Papua New Guinea and the Solomon Islands 37 , 38 , 39 , 40 highlights factors leading to poor maternal and perinatal outcomes, including stillbirth and early neonatal death. In Papua New Guinea, stillbirth is defined as a baby born without a heartbeat after 22 weeks gestation and weighing more than 500 g. 41 A recent study conducted in two provinces in Papua New Guinea identified a stillbirth rate of 23.4 per 1000 total births 37 and an early neonatal mortality rate (NMR-death within the first seven days) of 14 per 1000 livebirths.…”
Section: Maternal and Newborn Health Indicatorsmentioning
confidence: 99%
“…In Papua New Guinea, stillbirth is defined as a baby born without a heartbeat after 22 weeks gestation and weighing more than 500 g. 41 A recent study conducted in two provinces in Papua New Guinea identified a stillbirth rate of 23.4 per 1000 total births 37 and an early neonatal mortality rate (NMR-death within the first seven days) of 14 per 1000 livebirths. 38 A number of avoidable factors were identified among these adverse outcomes, with the majority related to poor intrapartum care and inadequate clinical management – at least one avoidable factor was identified for 94% of stillbirths. 27 Similarly, in the Solomon Islands, the stillbirth rate (defined as babies born after 28 weeks gestational age) is estimated to be 21.4–29.7 per 1000 livebirths.…”
Section: Maternal and Newborn Health Indicatorsmentioning
confidence: 99%